POLA ASUH ORANGTUA PEMULUNG DALAM ADAPTASI SOSIAL ANAK DI KELURAHAN MUARA FAJAR TIMUR, KABUPATEN RUMBAI BARAT, KOTA PEKANBARU - Sahara Alisyah; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the parenting pattern and the obstacles for scavengers in taking care of their school-age children. This study uses a descriptive qualitative method and involves 6 informants who are Muara Fajar scavengers who have lived for at least 5 years and have school-aged children. Determination of informants using purposive sampling technique. Data collection techniques were carried out by observation, interviews, and documentation. The result of this study indicate that the parenting applied by parents of scavengers at Muara Fajar landfill Pekanbaru City leads to democratic, authoritarian and permissive parenting. Democratic parenting is applied by 3 families, 2 tend to be authoritarian and only 1 applies permissive parenting. The obstacles or barriers to parenting scavengers are time and economic condition. Keywords: Parenting, Scavenger.adaptation